EPA protects against muscle damage in the mdx mouse model of Duchenne muscular dystrophy by promoting a shift from the M1 to M2 macrophage phenotype - de Carvalho, Samara Camaçari; Apolinário, Leticia Montanholi; Matheus, Selma Maria Michelin; Santo Neto, Humberto; Marques, Maria Julia (Elsevier, 2013)
In dystrophic mdx mice and in Duchenne muscular dystrophy, inflammation contributes to myonecrosis. Previously, we demonstrated that eicosapentaenoic acid (EPA) decreased inflammation and necrosis in dystrophic muscle. In the present study, we examined the effects of EPA and the corticoid deflazacort (DFZ) as modulators of M1 (iNOS-expressing cells) and M2 (CD206-expressing cells) macrophages. Mdx mice (14 days old) received EPA or DFZ for 16 days. The diaphragm, biceps brachii and quadriceps muscles were studied. Immunofluorescence, immunoblotting and ELISA assays showed that EPA increased interleucin-10, reduced interferon-γ and was more effective than DFZ in promoting a shift from M1 to M2. © 2013 Elsevier B.V. All rights reserved.
Keywords: Deflazacort; Dystrophy; EPA; Inflammation; M1 macrophages; M2 macrophages